The ACDEA and STAD techniques in the development of grade 9 student learning achievement on literature value analysis - Lachum, Jetsadakorn; Intasena, Autthapon (International Journal of Innovative Research and Scientific Studies, 2024)
The primary aims of the study were twofold: firstly, to examine the impact of employing the ACDEA (Assessment, Collaboration, Discussion, Exploration, and Analysis) and STAD (Student Teams Achievement Divisions) techniques on the academic performance of ninth-grade students in the analysis of literary values; and secondly, to evaluate the level of satisfaction among students regarding these pedagogical approaches. For this research, 26 grade 9 students from a public school in Thailand were selected through cluster random sampling. To collect data and measure outcomes, an integrated ACDEA and STAD learning management plan was employed, along with a literature evaluation achievement test and a satisfaction questionnaire. The gathered data underwent analysis using various statistical measures, including percentage, mean score, standard deviation, t-test, and effectiveness index, with the effectiveness criterion set at 80/80. The results of the study revealed that the combination of ACDEA and STAD techniques served as an effective learning management plan for the literature value analysis class. Students demonstrated notable improvements in their learning achievements as a result of the collaborative learning approach. Additionally, the students reported high levels of satisfaction with the learning experiences provided by this instructional strategy. The study’s contributions to the field of education are significant, as they provide empirical evidence supporting the implementation of ACDEA in language classrooms. Moreover, the collaborative learning model employed in this research holds potential implications for other classes with similar learner characteristics, thereby offering a valuable and practical pedagogical approach.